Sistem Pendukung Keputusan Pemilihan Juru Masak (koki) Menggunakan Metode Complex Proportional Assesment (COPRAS) - Alda Fadilla; Asyahri Hadi Nasyuha; Vina Winda Sari (JURIKOM (Jurnal Riset Komputer), 2022)
A cook (chef) is a person whose job is to make recipes, determine and measure cooking ingredients, cook, also serve a dish that is delicious, looks beautiful, and deserves to be paid. In determining the selection of cooks (cooks) manually at the Garuda restaurant, there are shortcomings that make mistakes in choosing cooks such as the difficulty of registering prospective cooks (cooks), the selection process is complicated, and it is difficult to choose a cook (cook) who fits the criteria set. has been set by the company. So to assist the selection of cooks (chef) at Garuda Restaurant, it is necessary to build a system that can assist restaurants in making decisions based on the problems they are facing. The many branches of Garuda restaurants that are spread in almost various regions and cities make restaurant managers and chief cooks will have different opinions to choose the best chef to be accepted in Garuda restaurant. Based on the description of the problems that occurred, for the selection of the best cook (chef) at the Garuda restaurant, a decision support system (SPK) is needed in making decisions so that the information becomes accurate so that it can facilitate the selection of cooks at the restaurant. In this study, the Complex Proportional Assessment (COPRAS) method was used for problem solving. This method can solve an efficient problem, because this method is used to find the best alternative based on the criteria. The results in the research on the selection of cooks (cooks) are alternative A07 with a value of 100 on behalf of  Rojali